Changing patterns of risk-sharing channels in the United States and the euro area - Jacopo Cimadomo; Massimo Giuliodori; Andras Lengyel; Haroon Mumtaz (European Central Bank (ECB), 2023)
In this paper, we assess how risk-sharing channels have evolved over time in the United States and the Euro Area, and whether they have operated as "complements" or "substitutes". In particular, we focus on the capital channel (income from cross-border ownership of productive assets), the credit channel (interstate or cross-country bank lending), and the fiscal channel (federal or international fiscal transfers). We offer three main contributions. First, we propose a time-varying parameter panel VAR model, with stochastic volatility, which allows us to formally quantify time variation in risk-sharing channels. Second, we develop a new test of the complementarity vs. substitutability hypothesis of the three risk-sharing channels, based on the correlation between the impulse responses of these channels to idiosyncratic output shocks. Third, for the United States, we explain time variation in the risk-sharing channels based on some key macroeconomic and financial variables.
Keywords: C11; C33; E21; E32; 330; Risk-sharing channels; time variation; complementarity; substitutability